Recommendations for identifying Crohn's disease patients with poor prognosis. (January 2013) - Miheller, Pal; Kiss, Lajos S; Juhasz, Mark; Mandel, Michael; Lakatos, Peter L
Clinical presentation at diagnosis and the disease course of Crohn's disease is heterogeneous and variable over time. The majority of patients with Crohn's disease will develop at least one stricturing or perforating complication requiring surgery during follow-up. New data support a change in the natural history of the disease associated with the advent of biologicals and tailored treatment strategy. Therefore, it is important to identify patients at risk for disease progression as soon as possible. In recent years, much emphasis has been placed on determining important predictive factors. Complex evaluation of factors such as clinical and endoscopic presentation, fecal, serological and routine laboratory tests, and genetic factors is needed. This review summarizes the available evidence and will hopefully assist clinicians when choosing a treatment strategy in everyday practice.